Strengthening of friction surfaces by using geomodifiers based on serpentines from the Dashukivka deposit - Bodu, Svіtlana; Andrieiev, Vyacheslav; Novoshytskyi, Anton (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is the process of improving the tribological characteristics of friction joints, in particular anti-wear and anti-burr properties. There is a practice of using serpentines, so-called "friction geomodifiers" (FGM), as special repair and restoration additives. Their use leads to a decrease in the coefficient of friction and temperatures in the contact zone; an increase in the mass of parts is observed, which indicates the restoration of worn surfaces. The mechanism of formation of new structures is still unclear. There are hypotheses that severe friction conditions initiate micrometallurgical processes at the atomic-crystalline level, as a result of which modified layers with unique tribological characteristics are formed on the surfaces. A comparative analysis of the main indicators of serpentines of the Dashukivka deposit in terms of chemical composition and structure showed their correspondence to widely known analogs but they were never used in such a capacity. According to the results of the tests, the additives have shown their effectiveness as geomodifiers of friction. Addition of 4 % serpentine to the lubricating composition based on I-20 A oil reduced the wear rate by 2–3 times, the friction moment by 15 %, compared to I-20 A without additives. An increase in surface microhardness was observed, from 6 GPa for the basic variant to 10 GPa, for the variant with FGM additives. It has been established that the use is most effective for heavily loaded friction pairs (ship fittings, hatch closures, etc.) as it increases the clamping load (from 600 to 1400 N for a pair of steel 45/ShKh15); with increasing load, the coefficient of friction and the rate of wear decrease. The results confirm the need to expand research into this area to solve the complex problem of increasing the reliability of tribojunctions. Keywords: repair and restoration technologies, friction geomodifiers, serpentine, heavily loaded friction pairs